VISUAL REPRESENTATION OF GOOD AND EVIL IN THE FILM THE SCHOOL FOR GOOD AND EVIL: A BARTHESIAN SEMIOTIC ANALYSIS - Khumairah, Tasya; Mustikawati, Yunitari; Sunra, La (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the visual representation of good and evil through character appearance in The School for Good and Evil (2022) using Roland Barthes’ semiotic theory. The research aims to reveal how visual signs construct meanings of goodness and evilness through the appearances of the characters in the film. Employing a qualitative descriptive method, the study uses selected screenshots featuring the visual appearances of major characters as the primary data. The analysis focuses on visual elements such as costumes, colors, hairstyles, accessories, facial expressions, and settings. The data are analyzed through Barthes’ three levels of signification: denotation, connotation, and myth (Barthes, 1972; Barthes, 1977). The findings indicate that good characters are visually represented through bright colors, elegant costumes, floral ornaments, soft lighting, and harmonious appearances. At the connotative level, these visual elements signify purity, kindness, beauty, nobility, and social prestige. In contrast, evil characters are represented through dark colors, gothic costumes, dramatic lighting, intimidating appearances, and threatening visual environments. These signs connote power, danger, aggression, rebellion, mystery, and moral threat. Furthermore, at the mythic level, the film reinforces conventional fairy-tale ideologies that associate physical beauty, elegance, and brightness with moral goodness, while associating darkness, monstrous appearances, and destructive power with moral evilness. This study contributes to semiotic film studies by demonstrating how visual signs embedded in character appearance communicate cultural meanings and ideological values related to morality in contemporary fantasy films.